2016
DOI: 10.1101/038570
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Information-dependent Enrichment Analysis Reveals Time-dependent Transcriptional Regulation of the Estrogen Pathway of Toxicity

Abstract: The twenty-first century vision for toxicology involves a transition away from high-dose animal studies and into in vitro and computational models. This movement requires mapping pathways of toxicity through an understanding of how in vitro systems respond to chemical perturbation. Uncovering transcription factors responsible for gene expression patterns is essential for defining pathways of toxicity, and ultimately, for determining chemical mode of action, through which a toxicant acts. Traditionally this is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Finally, we found that co-regulated gene clusters activated distinct groups of downstream biological processes, with the AHR-bound genomic cluster enriched for metabolic processes and the AHR-unbound non-genomic cluster primarily activating immune processes. This work, together with other recent studies of the PPARα and estrogen receptor pathways (McMullen et al 2014;Pendse et al 2016), illustrates the application of bioinformatic and statistical tools for reconstruction and analysis of the transcriptional regulatory cascades underlying cellular stress response.…”
Section: Discussionmentioning
confidence: 75%
“…Finally, we found that co-regulated gene clusters activated distinct groups of downstream biological processes, with the AHR-bound genomic cluster enriched for metabolic processes and the AHR-unbound non-genomic cluster primarily activating immune processes. This work, together with other recent studies of the PPARα and estrogen receptor pathways (McMullen et al 2014;Pendse et al 2016), illustrates the application of bioinformatic and statistical tools for reconstruction and analysis of the transcriptional regulatory cascades underlying cellular stress response.…”
Section: Discussionmentioning
confidence: 75%
“…ERa interacts with coactivators such as AP1 (cFos/ cJun), Sp1, and SNCG or, conversely, with co-repressors such as Sin3A to modify transcriptional responses to estrogen (Kushner et al 2000;Jiang et al 2003;Schultz et al 2003;Ellison-Zelski et al 2009;. Global gene expression profiling of breast tumor cell lines following E2 stimulation has identified as many as 1500 genes that are differentially regulated in response to estrogen (Katzenellenbogen et al 2000;Klinge 2000;Harrington et al 2003;Kininis & Kraus 2008;Pendse et al 2017). Only a small fraction of the differentially expressed genes are directly modulated by the ERa and ERb transcription factors (Madak-Erdogan et al 2008).…”
Section: Era Characterization and Signaling Overviewmentioning
confidence: 99%
“…Only a small fraction of the differentially expressed genes are directly modulated by the ERa and ERb transcription factors (Madak-Erdogan et al 2008). In addition to the ERs, other transcription factors including Foxm1, E2F1, E2F7, and ZNF217 are responsible for initiating expression of genes associated with cell cycle, cell growth, and differentiation (Shen et al 2011;Pendse et al 2017). This low degree of overlap between estrogen receptor binding and gene expression regulation is in sharp contrast to other nuclear receptors that have been shown to account for approximately half of the affected genes' expression (van der Meer et al 2010;McMullen et al 2014) and highlights the contribution of the so-called "nongenomic" signaling (i.e.…”
Section: Era Characterization and Signaling Overviewmentioning
confidence: 99%
“…CAAT, with one of the authors (TH) as principal investigator, promotes the use of advanced-omics and high-throughput technologies and supports the implementation of knowledge-based frameworks such as Pathways of Toxicity and Adverse Outcome Pathways (Hartung and McBride, 2011) and thus plays a key role in implementing the NAS Tox21 vision. A key goal of the Human Toxome Project is the development of tools for identification of pathways of toxicity (Kleensang et al, 2014) from multi-omics technologies (Maertens et al 2015Pendse et al, 2016) to feed into a systems toxicology approach (Hartung et al, 2012). The combination of orthogonal omics technologies has the advantage that the tremendous signal/noise problem of any omics technology is overcome.…”
Section: Strategic Planning In Toxicologymentioning
confidence: 99%